In-situ uniaxial drawing of poly-L-lactic acid (PLLA): Following the crystalline morphology development using time-resolved SAXS/WAXS. (10th April 2020) - Heeley, Ellen L.; Billimoria, Kharmen; Parsons, Nathan; Figiel, Łukasz; Keating, Elspeth M.; Cafolla, Conor T.; Crabb, Eleanor M.; Hughes, Darren J.
Abstract: Simultaneous synchrotron small- and wide-angle X-ray scattering (SAXS/WAXS) was used to follow the crystalline morphology evolution of poly-L- lactic acid (PLLA) during uniaxial deformation at various draw temperatures ( T d ). The mechanical behaviour of PLLA, was found to be strongly dependent on T d . 2D SAXS/WAXS data taken during the draw showed that at low T d s cavitation and voiding occurred and the initial crystallites underwent 'overdrawing' where they slip and are partially destroyed. SEM confirmed that surface voiding and cavitation had occurred at T d  = 60 and 65 °C but was absent at higher T d s. During the draw, no long-range macromolecular lamellar structure was seen in the SAXS, but small crystallites of the disordered α′ crystal form of PLLA were observed in the WAXS at all T d s. The PLLA samples were then step annealed in a second processing stage (post-draw) to develop the oriented crystalline lamellar structure and increase the amount of the stable α crystalline form. SAXS/WAXS data showed that a highly oriented lamellar stack macrostructure developed on annealing, with increased crystallite size and crystallinity at all T d s. Furthermore, step annealing drove the crystalline transition in all samples from the disordered α′ crystal form to the stable α crystal form. Therefore, varying pre- and post-processing parameters can significantly influence the mechanical properties, orientation, crystalline morphology and crystal phase transition of the final PLLA material. Graphical abstract: Image 1 Highlights: SAXS/WAXS was used to follow the morphology development during drawing of PLLA. The mechanical behaviour of PLLA depends strongly on draw temperature. The disordered α′ crystal form was seen pre-and post-draw at all draw temperatures. Annealing samples post-draw drove the α′-α crystal form transition. An oriented lamellar macromorphology developed on annealing.